Penggunaan Verba Doushi Benkyousuru, Manabu, Renshuusuru, dan Narau terhadap Pasangan Nominanya - Asmarani, Dhaniar (Humaniora, 2015)
Research discusses the different use of Japanese verbs benkyousuru, manabu, renshuusuru, and narau associated with the use of nouns attaching to the verbs. Data corpus was taken from magazine Jakarta Communication Club: Apa Kabar, Vol 50, 2010. The research applied qualitative study using descriptive analysis method. Research aims to give better understanding for Japanese language learners in using the Japanese verbs benkyousuru, manabu, renshuusuru, narau. Besides, the learners can use these verbs properly as well. Result of the research shows that the verbs have different use and also different use of nouns attaching on the verbs.